Gender equity in Australian health leadership - Cohn, Amanda; Cubitt, Mya; Goh, Anita; Hempenstall, Allison; Hoffman, Rebekah; Lai, Christine; Munro, Jane; Silvester, Carly; Skinner, Clare; Verran, Deborah; Walter, Jordan (Asia Pacific journal of health management, 2021)
Objective: To ascertain the gender distribution across public health boards in Australia. Design and setting: Analysis of data and information obtained from a cross sectional audit of online publicly listed health boards within Australia from October to December 2019. Results: The majority of public health boards have close to equal representation of women as board members however women are underrepresented in Chair roles. Victoria has significantly more women on health boards, whereas New South Wales has significantly less women on health boards and in Chair positions. Conclusions: Further efforts are required to drive gender equity in senior leadership roles in public health boards across Australia.